Venezia dopo Venezia: economia e demografia urbana nel novecento - Giovanni Favero (Laboratoire Italien)
Subject of this paper is the relationship between the urban population, the inhabitants (many or few, young or old, male or female) who live in the Venice island, and the economic functions that the city has taken or has been assigned during the 20th century. The author in fact believes that the answer to some crucial questions concerning the city of today, asking how Venice could become what it is today, should be researched exactely in the interplay between projects of displacement and resettlement of the population, related to an idea of the historical city that becomes unchangeable in its own structure in the mid century.